2017
DOI: 10.1111/ecc.12727
|View full text |Cite
|
Sign up to set email alerts
|

How do the characteristics of breast cancer diagnostic assessment programmes influence service delivery: A mixed methods study

Abstract: Diagnostic assessment programmes (DAPs) coordinate multidisciplinary teamwork (MDT), and improve wait times and patient satisfaction. No research has established optimal DAP design. This study explored how DAP characteristics influence service delivery. A mixed methods case study of four breast cancer DAPs was conducted including qualitative interviews with health‐care providers and retrospective chart review. Data were integrated using multiple approaches. Twenty‐three providers were interviewed; 411 medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Efforts are also needed to ensure consistency in language across differing specialties. In other research, we found that multidisciplinary teamwork was enhanced when coordinated through integrated programs, staff were co‐located, patient navigators mediated patient transitions between clinicians, and other activities such as team meetings supported clinician efficiency . Future research could investigate whether these or other strategies could harmonize DCIS language.…”
Section: Discussionmentioning
confidence: 81%
“…Efforts are also needed to ensure consistency in language across differing specialties. In other research, we found that multidisciplinary teamwork was enhanced when coordinated through integrated programs, staff were co‐located, patient navigators mediated patient transitions between clinicians, and other activities such as team meetings supported clinician efficiency . Future research could investigate whether these or other strategies could harmonize DCIS language.…”
Section: Discussionmentioning
confidence: 81%
“…Surgery is not integrated into most provincial cancer bodies and there are no explicit roles to oversee the systematic evaluation and regulation of cancer surgery in most provinces. As a result, there is clear variation in breast cancer outcomes across the country [ 1 , 2 , 3 , 4 , 5 ]. Recently, the Canadian Partnership Against Cancer (CPAC) published pan-Canadian evidence-based surgical standards for the care of the breast cancer patient [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study is part of a larger study exploring whether and how dap characteristics influence diagnostic service delivery measures such as wait time from referral to confirmed diagnosis and number of visits 13 . We are equally interested in exploring whether daps are cost-effective.…”
Section: Introductionmentioning
confidence: 99%